Corrosion challenges in supercritical CO2 transportation, storage, and utilization—a review. (June 2023) - Sun, Haofei; Wang, Haoxiang; Zeng, Yimin; Liu, Jing
Abstract: Research activities for Carbon capture, utilization, and storage (CCUS) have been rapidly growing due to climate goals and investment opportunities over the past few decades. This work provides an overview of recent corrosion research progress under supercritical CO2 (s-CO2 ) conditions, focusing on the wet s-CO2 rich phase and s-CO2 -saturated aqueous phase with various impurities. Major corrosion damages on core components of supercritical CO2 transportation, storage, and utilization systems occur in these environments. In various s-CO2 environments, the structure and integrity of corrosion layers play a significant role in the overall corrosion kinetics. Moreover, the understanding of corrosion kinetics laws in s-CO2 environments is currently inadequate, and there is considerable variability in reported corrosion outcomes. Most of the existing studies were conducted in static autoclaves with different exposure durations, making the obtained result lack consistency and high reliability for real operation consideration. In addition, significant knowledge gaps are identified and discussed. Potential research paths, including constructing novel iso-corrosion diagrams, understanding the protection and failure mechanisms of corrosion product layers, improving experimental methods, and developing standards and artificial intelligence approaches from both engineering application and fundamental scientific perspectives, are proposed. This review shall provide useful information and insights for the further development and deployment of the CCUS technology. Highlights: Overview of corrosion research in supercritical CO2 conditions from a data-oriented perspective. Discussing operating conditions and materials of construction used in s-CO2 transportation, storage and utilization systems. Analyses of corrosion data obtained from s-CO2 rich phase and s–CO2 –saturated aqueous phase with various impurities. Highlighting the importance of establishing a standard testing methodology for in-situ measurements. Importance of the structure and integrity of corrosion layers on corrosion kinetics.